The Politics of Indonesia’s Renewable Energy Policy - Supriyanto, Eko Eddya (Langgas: Jurnal Studi Pembangunan, 2024)
Indonesia's natural landscape of land and sea is a very abundant energy resource. Indonesia has enormous opportunities because of its gift of natural resources, which can be used as renewable energy sources. This study comes from secondary data to support arguments, and data collection uses library research by collecting material from books, journals, laws and regulations, and other literature. The data analysis technique uses descriptive language by describing the data, which is then analyzed to describe an explanation of the data. This research explains the potential of Indonesia's energy resources, especially renewable energy, and the politics of Indonesia's renewable energy policy, which targets an energy mix of 44% by 2030. This research concludes that renewable energy policy has obstacles, including weak control. Renewable energy resource exploration technology, expensive machines for exploring energy resources, and the formulation of laws related to new renewable energy have not yet become a priority.